MENCARI WARISAN NABI DI INDONESIA DALAM PERSPEKTIF SEJARAH - Djazimah, Nurul (Jurnal Studia Insania, 2015)
Indonesia is a country with the worldâs third largest population; about 90 percent of the population is Muslims.Â The history of the Islam in this country can be traced back to descendants of the prophet Muhammad. TheyÂ played an important role in disseminating Islamic teachings in the archipelago. Until now descandants of theÂ prophet still engage in Islamic preaching activities, understanding the legacy of the prophet from historicalÂ perspective is instructive, for that will help clarify the making of Muslim civilition in the archipelago. TheÂ prophet sent his companions to the area now known as Indonesia. His predecesors continued this tradition ofÂ sending companions in preaching missions nost notably in the time Utsman ibn Affan. The Islamic spiritualÂ link with Indonesia was concrete: one preserved clothing of the prophet and a flag used in one of this own battlesÂ were given to the Sultan of Banten as gifts. Indeed, the community of Islamic believers shares the legacy of theÂ prophet regardless of their orgins. Most prominently among them have been the Islamic preachers and MuslimÂ warriors.